Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 4 - Section 4.3 - Solving Systems of Linear Equations by Addition - Exercise Set: 27

Answer

$x=\dfrac{3}{2}$ $y=3$

Work Step by Step

$\begin{cases}\dfrac{x}{3}+\dfrac{y}{6}=1\\\dfrac{x}{2}-\dfrac{y}{4}=0\end{cases}$ Multiply the first equation by $6$ and the second equation by $4$ to remove the fractions: $\begin{cases}2x+y=6\\2x-y=0\end{cases}$ Add the two equations to remove the $y$: $4x=6$ Solve for $x$: $x=\dfrac{6}{4}=\dfrac{3}{2}$ Substitute $x=\dfrac{3}{2}$ in the first equation: $2\Big(\dfrac{3}{2}\Big)+y=6$ Solve for $y$: $3+y=6$ $y=6-3=3$ Our two solutions are: $x=\dfrac{3}{2}$ $y=3$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.